ANALISIS TINGKAT PELAYANAN JALAN MENGGUNAKAN PERANGKAT LUNAK VISSIM PADA SIMPANG BERSINYAL CISALAK, KOTA DEPOK - Dadang Suyadi; Rakha Imaulanda (Universitas Negeri Jakarta, 2019)
The intersection of the Cisalak I toll gate in Depok City is the intersection that connects the road. Ir. H. Juanda, Jalan Raya Bogor, Jalan Gas Alam, and of course the Cisalak I highway exit & exit. By having 6 intersection arms, of course there are many traffic conflicts that occur at the Cisalak I toll gate intersection, one of which is a delay in the intersection arm long so that congestion in each intersection during rush hour always occurs and coupled with the cycle time of the traffic light which takes quite a long time so the long queue occurs. The purpose of this study is to know more about the performance of the traffic. The method used is to observe directly to the research location by observing the volume of vehicles with various types, the phase current of the vehicle passing at the intersection, and the cycle time of the traffic light, and by using Vissim software as modeling and getting the results of the count. The results of the study found capacity on the Bogor Highway (Jakarta direction) with a total of 771.69 , Jalan Ir. H. Juanda is 542.92, Bogor Highway (Bogor direction) is 612.21, and Cijago / Cisalak & Natural Gas Toll Road is 538. and the value of degree of saturation in each intersection is Highway Bogor (direction Jakarta) amounting to 2.96, Jalan Ir. H. Juanda is 3.52, Bogor Highway (Bogor direction) is 2.77, and Cijago / Cisalak & Gas Alam Toll Road is 2.95, so the level of service results in all F crossing arms which means the congestion condition takes up the duration long enough.